2013
DOI: 10.1523/jneurosci.4367-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Intracellular Aβ42Amyloid Oligomers Involves Ca2+Release from the Endoplasmic Reticulum by Stimulated Production of Inositol Trisphosphate

Abstract: Oligomeric forms of Aβ peptides associated with Alzheimer`s disease (AD) disrupt cellular Ca2+ regulation by liberating Ca2+ into the cytosol from both extracellular and intracellular sources. We elucidated the actions of intracellular Aβ42 by imaging Ca2+ responses to injections of Aβ oligomers into Xenopus oocytes. Two types of signal were observed: (i) local, 'channel-like' transients dependent on extracellular Ca2+ influx, which resembled signals from amlyoid pores formed by extracellular application of ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
153
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(166 citation statements)
references
References 56 publications
(69 reference statements)
10
153
3
Order By: Relevance
“…In addition to ER RyR3, inositol 1, 4, 5-triphosphate receptor (IP3R) is also linked to ER Ca 2? release by Ab [74].…”
Section: Cellular Defects In Ab Neurotoxicitymentioning
confidence: 99%
“…In addition to ER RyR3, inositol 1, 4, 5-triphosphate receptor (IP3R) is also linked to ER Ca 2? release by Ab [74].…”
Section: Cellular Defects In Ab Neurotoxicitymentioning
confidence: 99%
“…release from the endoplasmic reticulum (ER) Ca 2+ store [13]. The "β-amyloid calcium pore" hypothesis has evolved into β-amyloid-induced modulation of physiologically-relevant Ca 2+ homeostatic/signalling pathways.…”
Section: +mentioning
confidence: 99%
“…Costa et al have demonstrated that Ab-induced ER stress can be effectively inhibited by ifenprodil, an antagonist of GluN2B subunits, which could be a potential therapeutic strategy for AD (Costa et al, 2012). Intracellular Ab oligomers are also shown to disrupt Ca 2+ handling of intracellular Ca 2+ stores, especially ERs (Demuro and Parker, 2013). They are believed to be produced from APP residing on the ER and in other intracellular compartments, as well as by uptake from the extracellular space (Mohamed and Posse de Chaves, 2011).…”
Section: Ab and App: Disruption Of Er Ca 2+ Homeostasis By The Ab Pepmentioning
confidence: 99%
“…Ab 42 oligomer pores can also be formed in the membranes of intracellular organelles and result in Ca 2+ leakage into the cytosol; the disruption is comparatively mild (Demuro et al, 2005;Demuro and Parker, 2013). Most research has demonstrated that Ab oligomers enhance Ca 2+ liberation from the ER, mainly by altering Ca 2+ release via IP 3 Rs and RyRs (Kelliher et al, 1999;Ferreiro et al, 2004;Stutzmann et al, 2006;Schapansky et al, 2007).…”
Section: Ab and App: Disruption Of Er Ca 2+ Homeostasis By The Ab Pepmentioning
confidence: 99%
See 1 more Smart Citation